Nutritional supplementation for vitamin B12 and vitamin K2 deficiency following ileostomy or colostomy formation. (1st May 2020) - Mantle, David
Abstract : Most dietary vitamins and minerals are absorbed from the duodenal and jejunal sections of the small bowel. The exceptions are vitamin B12 and vitamin K2, which are absorbed from the terminal ileum and colon respectively. Patients who have undergone ileostomy or colostomy procedures are at risk of deficiency of these vitamins, with associated risk of developing anaemia and nervous system dysfunction (vitamin B12), and bone weakening and cardiovascular disease (vitamin K2). Patients should therefore be monitored for deficiency of these vitamins, which may develop over a protracted period of time. Patients lacking the terminal ileum or colon can still absorb supplemental vitamins B12 or K2 given orally, provided a sufficient loading dose is given to facilitate absorption from the remaining gastrointestinal tract.